89.6k views
1 vote
Solve for x
3(x - 2) = 6x - 12


1 Answer

3 votes

Answer:

The answer is 2

Explanation:

Here's how I got it:

3(x - 2) = 6x - 12

Multiply 3 times x and 3 times 2, this is what you would get

3x - 6 = 6x - 12

Then, subtract the lowest x with the bigger X, this way you would have x on one side:

3x - 6 = 6x - 12

-3x -3x

This is what you should have after this:

-6 = 3x - 12

Now, to get the variable (letter that represents a number) by itself, you have to add 12 to both sides like this:

-6 = 3x - 12

+12 +12

You would get this:

6 = 3x

Finally, you have to get x by itself, so you have to divide 3 on both sides like this

6/3 = 3/3 x

That's why, your answer is 2

User Ecs
by
4.5k points